1998
DOI: 10.1073/pnas.95.16.9099
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structure of a recombinant α E C domain from human fibrinogen-420

Abstract: The crystal structure of a recombinant ␣ E C domain from human fibrinogen-420 has been determined at a resolution of 2.1 Å. The protein, which corresponds to the carboxyl domain of the ␣ E chain, was expressed in and purified from Pichia pastoris cells. Felicitously, during crystallization an amino-terminal segment was removed, apparently by a contaminating protease, allowing the 201-residue remaining parent body to crystallize. An x-ray structure was determined by molecular replacement. The electron density w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
39
0
1

Year Published

2000
2000
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(42 citation statements)
references
References 33 publications
(23 reference statements)
2
39
0
1
Order By: Relevance
“…Interestingly, the EC sequence is highly conserved among vertebrates with 93.2% homology in rats, 70.3% in Xenopus and 52.2% in lamprey fish compared with humans [5]. Its structure has been elucidated through crystallography [6], but its functional characteristics have been poorly described. The EC region is susceptible to early proteolysis by plasmin [7] and can act as a ligand for neutrophils and monocytes via  M  2 and  X  2 integrins [8].…”
Section: Fibrinogen Ecmentioning
confidence: 99%
“…Interestingly, the EC sequence is highly conserved among vertebrates with 93.2% homology in rats, 70.3% in Xenopus and 52.2% in lamprey fish compared with humans [5]. Its structure has been elucidated through crystallography [6], but its functional characteristics have been poorly described. The EC region is susceptible to early proteolysis by plasmin [7] and can act as a ligand for neutrophils and monocytes via  M  2 and  X  2 integrins [8].…”
Section: Fibrinogen Ecmentioning
confidence: 99%
“…The majority of the D region is formed by the C-terminal portions of the ␤-and ␥-chains folded into similar structures (so-called ␤C-and ␥C-domains) (3). The alternatively spliced ␣ E C-domains (present in a small population of Fg molecules) represent the extensions of the ␣-chains and have a high structural homology to ␤C and ␥C (4). Two unrelated sequences in the ␥C-domain, ␥190 -202 (GWTVFQKRLDGS) and ␥377-395 (YSMKKTT-MKIIPFNRLTIG), have been proposed to be sites that mediate Fg binding to ␣ M ␤ 2 (5,6).…”
mentioning
confidence: 99%
“…18,21,22 Because ␥C shares about 40% amino acid identity with the ␣ E C domain of 30 and the 2 domains are folded into almost identical structures, 33 we tested adhesion of ␣ M ␤ 2 -expressing cells to recombinant ␣ E C. As shown in Figure 2A, when recombinant proteins were immobilized on tissue culture-treated polystyrene plates, both proteins supported efficient adhesion of ␣ M ␤ 2 -transfected HEK 293 cells. Adhesion depended on the concentration used, and similar numbers of cells adhered to each protein.…”
Section: Resultsmentioning
confidence: 99%
“…It is known that ␣ E C and ␥C share about 40% of amino acid identity, 30 and analyses of x-ray structures revealed that folding of the ␣ E C domain closely resembles that of ␥C. [32][33][34] In this study, we analyzed the interaction of ␣ E C with leukocyte integrins. We found that the ␣ E C domain of Fg-420 is a ligand for ␣ M ␤ 2 and ␣ X ␤ 2 capable of mediating strong leukocyte adhesion and promoting directed migration of leukocytes.…”
Section: Introductionmentioning
confidence: 99%